Gender differences in time-frequency EMG analysis of unanticipated cutting maneuvers - Beaulieu, M. L.; Lamontagne, M.; Xu, L. (Medicine & Science in Sports & Exercise, 2008)
Purpose: The purpose of this study is to compare the time-frequency characteristic, using nonlinearly scaled wavelets, of the EMG signal as well as the three-dimensional (3D) knee kinematics of female and male elite soccer players performing an unanticipated cutting maneuver.